Analisa Pengaruh Kotoran Organik pada Pasir Kasar Sungai Batanghari terhadap Kuat Tekan Beton - Andro Daniel G; Suhendra Suhendra; Wari Dony; Dwitya Okky Azanna (Universitas Batanghari Jambi, 2023)
The organic content contained in the sand can affect the quality and improvement of the concrete which will slow down the concrete process. Sand originating from the Batanghari watershed is pretty much inspected in the laboratory of the Faculty of Engineering. The design of the concrete shows that the organic content of sand originating from the Batanghari river basin is quite high. There are 2 variations of the concrete test object, unwashed sand and washed sand, The source of sand from the Batanghaari river Sembubuk village, Kec. Jambi Outer City District. Muaro Jambi which refers to the British standard and ASTM C-33. The aim is to get the levels of organic impurities contained in the coarse sand of the Batanghari river and to determine the effect of medium sand on the compressive strength of concrete. The implementation method refers to SNI 7656:2012 regarding the test method for the procedure for selecting mixtures for normal concrete, heavy concrete, and mass concrete. The concrete test object is in the form of a cylinder with a size of 15 cm x 30 cm. the results of the organic dirt test for coarse sand on the Batanghari Jambi river, namely the unwashed sand is number 4 and for washed sand it is number 2 on the organic plate. The results showed that the average compressive strength of concrete at the age of 28 days on unwashed sand with a compressive strength of 26.28 MPa and at the age of 28 on sand washed with a compressive strength of 29.15 MPa.